Pengaruh Gaya Hidup (lifestyle), Harga, Promosi terhadap Pemilihan Tempat Tujuan Wisata (destination) Studi Kasus pada Konsumen Artojaya Tour & Travel Surabaya - Metha Nilarisma Dewi (Jurnal Strategi Pemasaran, 2015)
Nowadays, the service industry competition is very interesting to be discussed, especially industry which provides tour and travel services. This kind of competition becomes a trigger to the people’s lifestyle. The problem is, for consumers who have middle-high income, can go on vacation when it comes to school holiday. In fact, that kind of behaviour has become their lifestyles because they are willing to buy something expensive to get services which they like. However, their lifestyles, price and promotion will indirectly affect consumers in the selection of a tourist destination.This research is using sample from ArtoJaya’s consumers. The sampling technique is using purposive technique and selected sample with consumers who did transactions or purchases for the last three month. On the other hand, the analysis technique is using Multiple Linear Regression with the total 200 respondents. The 100 respondents will facilitate in seeing the role of lifestyle price and promotion against the destination which is going to be tested.